Levantamento da qualidade de sementes de soja de três regiões do estado do Maranhão - Santos, Jodson Moraes (2016)
The seed is the main agricultural input for the implantation of a crop when seeking to achieve quality and productivity. The production, maintenance of physiological and sanitary quality of soybean seeds (Glycine max (L.) Merrill), during its storage in the new agricultural frontier, MAPITOBA, is challenging for regarding the cerrado, a low latitude edaphoclimatic region (between 0 and 10 o ), with high temperatures and relative air humidity, elevated pluviometry precipitation indexes, elements which determine the high incidence of fungi and damage the seed during its physiological maturity and storage. This environment has become worrisome due to the factors that lead to the imminent deterioration of the seeds, especiall y in the state of Maranhão, Brazil. Thus, with this work, we aimed at surveying the physiological and sanitary quality of soybean seeds produced in three regions of the state of Maranhão (southwest, south and north), of the 2013/2014 harvest. The experiment was qualitative exploratory comparing the regions before and after six months of storage. We used the R software and compared the means with the Tukey test (5% of probability), building a boxplot for data exploration. For the evaluation of the physiological quality of the seeds, we determined water content (%), germination (%), first germination count (%), emergence (%), emergence speed index, accelerated aging (%), electric conductivity, tetrazolium (vigor and feasibility) and sanitary tests by means of the Blotter-test. The lots of the cultivars maintained the water contents in the range of 10% during the six months of storage. The samples of the recently harvested seeds and of those harvested after six months of storage in the southern region of Maranhã o presented better physiological and sanitary quality. There was also reduction in the quality of seeds produced and stored in the northern and southwestern regions after six months of storage. The results of the sanitary test indicate that there was incid ence of field and storage pathogensassociated to the seeds, with genera Colletotrichum truncatum, Cercospora kikuchii, Fusarium sp, Penicullium sp and Aspergillus sp presenting the highest incidences.